P82 Anti-phospholipid antibodies and renal involvement are the main features associated with adverse pregnancy outcomes in patients with systemic lupus erythematosus – a long-term longitudinal study in Southern Sweden. (23rd March 2020) - Saleh, Muna; Jönsen, Andreas; Bengtsson, Anders; Sjöwall, Christopher; Compagno, Michele
Abstract : Background: Systemic Lupus Erythematosus (SLE) affects mostly women in childbearing age. Modern management of SLE patients has improved the pregnancy outcomes over the last decades. However, there is still an increased risk of maternal, fetal and neonatal complications. In this longitudinal follow-up of pregnant women affected by SLE, we aimed to investigate which clinical and immunological features may predict for the occurrence of adverse pregnancy outcomes (APOs). Methods: We investigated the outcome of 59 pregnancies in 28 SLE patients who have had one or more pregnancies, between 2002 and 2018. Longitudinal clinical and laboratory data from rheumatology, obstetrics and neonatal units were collected and analyzed. We assessed the association between the presence of SLE-related clinical and immunological features and the occurrence of adverse pregnancy outcomes. Results: We recorded 52 APOs in 18 (64.3%) patients. The 59 investigated gestations resulted in 44 (31 vaginal and 13 C-sections) deliveries, 8 (18.2%) before the 37th gestational week, 13 (22%) early miscarriages and 2 (3.4%) induced abortions. HELLP syndrome and preeclampsia complicated 1 (2.3%) and 11 (25%) gestations, respectively. Moreover, 10 (22.7%) newborns had low birth weight, 5 (11.4%) fetuses had intra-uterine growth restriction, whereof 1 (2.3%) resulted in small for gestational age neonate. Neonatal lupus occurred in 1 (2.3%) baby. Previous lupus nephritis was associated with higher risk of APOs overall (OR=5.9- p = 0.01 ), in particular impaired fetal growth (OR=16.6- p = 0.01 ). The presence of anti-phospholipid antibodies was also associated with higher risk of APOs overall (OR=4.5- p = 0.01 ). In particular, the occurrence of preterm delivery and the incidence of miscarriage were associated with the presence during pregnancy of anti-cardiolipin antibodies (OR=6.8- p = 0.03 ) and with concomitant anti-phospholipid syndrome (APS) (OR=3.3- p = 0.04 ), respectively. Conclusions: Several different APOs occur in the majority of SLE-patients, in particular in those with renal involvement, APS and presence of anti-phospholipid antibodies.